TREATMENTS OF PLASMA CORONA RADIATION ON SEAWEED Gracilaria Verrucosa (HUDSON) PAPENFUSS: Efforts to increase growth and biomass - Filemon Jalu N Putra; Zaenul Muhlisin; Sapto P. Putro (Chemical Engineering Diponegoro University, 2015)
Gracilaria verrucosa (Hudson) Papenfuss has great potential to be farmed in the water resources in Indonesia. As natural resource, the weed has a major contribution in the field of industry both for human food and health. Efforts have been done intensively to increase the production capacity to meet the market demand especially gelatin, both national and international market. One of them is the application of plasma corona irradiation treatments on the weed to improve developmental pathways. The concept of plasma irradiation performed at atmospheric conditions may impact on nitrogen intrusion pathway that is important element in the growth of the weed. The aims of this study are to assess the potential impact of plasma irradiation in improving the growth of G. verrucosa and thus increase their biomass production. The treatments were done using five different duration of plasma irradiation, which were 2, 4, 6, 8, and 10 minutes at a 0,5mA stable source of voltage and 8kV of electrical current. Observations of growth rate include thallus length and biomass of G. verrucosa , that was observed every week for 28 days. The result showed that the growth of weed exhibited better than those without radiation. The best growth was reached in the group of treatment of 8 minutes irradiation, exhibited 65,91g of biomass and 9.5515% growth rate and length of thallus reached 22,33 cm and daily growth rate of 2.9759%. The lowest growth of the weed occurred in the treatment of 10 minutes irradiation, which was 44,82 g biomass, 8.123% growth rate, 17,13 cm thallus length with a daily growth rate of 1.9942%